2021
DOI: 10.1039/d1fo00576f
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside extract from ginseng extends lifespan and health span inCaenorhabditis elegans

Abstract: Ginsenoside extract from ginseng extends lifespan and health span in Caenorhabditis elegans through activating NRF2/SKN-1, SIRT1/SIR 2.1, and FOXO/DAF-16 signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Rg1 and Re exhibited similar anti-aging effects as TGGR in Drosophila . Consistent with other studies, Rg1 and Re are the major components of Panax ginseng, which prolongs the lifespan of C. elegans ( Wang et al, 2021 ), and Rg1 prevents cognitive impairment and hippocampal senescence in a rat model of aging ( Zhou et al, 2020 ). In future studies, specific anti-aging effects of single saponins should be clarified, and synergistic studies of each saponin based on clear molecular mechanisms should be examined.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Rg1 and Re exhibited similar anti-aging effects as TGGR in Drosophila . Consistent with other studies, Rg1 and Re are the major components of Panax ginseng, which prolongs the lifespan of C. elegans ( Wang et al, 2021 ), and Rg1 prevents cognitive impairment and hippocampal senescence in a rat model of aging ( Zhou et al, 2020 ). In future studies, specific anti-aging effects of single saponins should be clarified, and synergistic studies of each saponin based on clear molecular mechanisms should be examined.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, ginsenosides have the potential to be used as an alternative natural medicine for anti-aging and life-prolonging effects. A recent study reported that total ginsenoside extract can prolong the lifespan and healthy lifespan of Caenorhabditis elegans ( C. elegans ) by activating anti-oxidation signaling pathways ( Wang et al, 2021 ). However, the use of ginsenoside extract for delaying human aging, its anti-aging activities, optimal dosage and means of administration in different species need further investigation, and its multi-target mechanism of action needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng extract can resist the negative effects of heat stress [16]. Studies on C. elegans have shown the promising efficacy of certain saponins in reversing age-related declines via antioxidant regulation and longevity signaling pathways [17]. Sun Ginseng can effectively inhibit the proliferation and differentiation of adipocytes and can reduce the fat accumulation in C. elegans, which also suggests that the active substance in ginseng that plays the function of reducing the fat accumulation may be ginsenosides [18].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the Nrf2 signaling pathway plays an important role in the antioxidant process ( 29 ). The antioxidant activity is closely related with the traditional use of Baizhu for improving longevity ( 30 ).…”
Section: Resultsmentioning
confidence: 99%